2014
DOI: 10.1007/s40516-014-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study and Multi-Criteria Optimization in Laser Cladding by a High Power Direct Diode Laser

Abstract: In laser cladding, the performance of the deposited layers subjected to severe working conditions (e.g., wear and high temperature conditions) depends on the mechanical properties, the metallurgical bond to the substrate, and the percentage of dilution. The clad geometry and mechanical characteristics of the deposited layer are influenced greatly by the type of laser used as a heat source and process parameters used. Nowadays, the quality of fabricated coating by laser cladding and the efficiency of this proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Analysis of variance (ANOVA) was used to verify and analyze the fitted models. The significance level (α) was set at 0.05, which is a commonly used level in significance tests [9,20,21]. Experimental validation to verify that the optimized processing parameters and substrate size was conducted with targeting on the desired geometric characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of variance (ANOVA) was used to verify and analyze the fitted models. The significance level (α) was set at 0.05, which is a commonly used level in significance tests [9,20,21]. Experimental validation to verify that the optimized processing parameters and substrate size was conducted with targeting on the desired geometric characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Farahmand and Kovacevic used response surface methodology embedded with a central composite design module to investigate the influences of laser power, powder flow rate, and scanning speed on the clad height, heat-affected zone height, and clad microhardness. A multiple regression analysis was used to establish the models, and the accuracy of the models was validated by analysis of variance [9]. Laser cladding on curved surfaces has also drawn research attention because of its demand in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farahmand and Kovacevic [16] used a predictive approach to assess the influence of input parameters on geometry and microhardness of the deposited beads, established the dependency relationships between the inputs and outputs and optimized the deposition process parameters of AISI H13. They concluded that when increasing the laser scanning speed (mm/s), the bead height and HAZ (heat affected zone) decreased, while microhardness increased.…”
Section: Introductionmentioning
confidence: 99%
“…They also used CCD/RSM/ANOVA to identify statistical relationships between input parameters and output variables and optimal processing parameters identification. This study used similar approach of previous works (Farahmand and Kovacevic, 2014) but using different powder materials, which could be considered an extended research. They concluded that the powder flow (g/min), the gas flow rate (SCFH) and the interaction between the gas flow rate and the standoff distance (mm) were the most significant factors affecting the bead height (mm), while the laser power (W) was the factor most affected the bead width (mm).…”
Section: Introductionmentioning
confidence: 99%